The increasing incidence of surgically treated quadriceps tendon ruptures - Reito, Aleksi; Paloneva, Juha; Mattila, Ville M.; Launonen, Antti P. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2019)
Purpose Due to increased life expectancy and a more active life style of the older people, we hypothesised that the incidence of quadriceps tendon rupture (QTR) is higher than previously reported. The objective of this nationwide population-based study was to investigate the annual incidence of QTR in patients who underwent operative treatment in Finland between 1997 and 2014. Methods The Finnish National Hospital Discharge Register was searched for all adult patients who had undergone surgical treatment for QTR during the study period. Population-based annual incidence and incidence trends for surgically treated QTR were calculated. Results During the study period, 1343 QTR surgeries were performed. Of these, 90% were performed on male patients. The incidence of QTR increased by 411% from 0.55 to 2.82 per 100,000 person-years from 1997 to 2014. The average yearly increase in the number of surgeries was 9.0%. In male patients, the incidence of QTR increased by 490% and in female patients by 121%. The mean age of the male patients increased during the study period from 50 to 59 years. Conclusions Based on the data from the Finnish National Hospital Discharge Register, the annual incidence of QTR increased by over 400% during the 18-year study period. The average age of the patients also increased. Because QTR is only very rarely treated without surgery, the results of our study can be considered to be a reliable estimate of the increase in the incidence of this condition. There is an urgent need to establish the risk factors associated with QTR and to also establish the optimal surgical technique. Level of evidence IV.